A criterion for slip transfer at grain boundaries in Al. (15th March 2020) - Alizadeh, R.; Peña-Ortega, M.; Bieler, T.R.; LLorca, J.
Abstract: The slip transfer phenomenon was studied at the grain boundaries of pure Aluminum by means of slip trace analysis. Either slip transfer or blocked slip was analyzed in more than 250 grain boundaries and the likelihood of slip transfer between two slip systems across the boundary was assessed. The experimental results indicate that slip transfer was very likely to occur if the residual Burgers vector, ∆b, was below 0.35 b and the Luster–Morris parameter was higher than 0.9, and that the ratio of the Luster–Morris parameter and the residual Burgers vector has a threshold above which slip transfer is probable. Graphical abstract: Image, graphical abstract